2014
DOI: 10.1007/s00264-014-2587-4
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day readmission rate and discharge status following total hip arthroplasty using the supercapsular percutaneously-assisted total hip surgical technique

Abstract: Purpose Recent studies have reported nearly 40 % of costs associated with a 30-day episode-of-care for total joint replacements are due to post-discharge activities and 81 % of those are specifically due to unplanned readmissions and discharging patients to post-acute care facilities. The purpose of this study was to determine these two key variables for total hip arthroplasty (THA) patients implanted using a tissuesparing surgical technique and to see how these values compare to those previously reported in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 14 publications
(21 reference statements)
4
41
0
Order By: Relevance
“…Due to the identical anticoagulation and transfusion protocols, the reduction in transfusions can be at least partly attributed to the tissue-sparing nature of the SuperPath procedure. This finding also agrees with the described recent multicentre study showing a substantial reduction in transfusion rates for this technique when compared to the national average in the United States [4]. Transfusions have been associated with increased complications, such as infections [8,9].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Due to the identical anticoagulation and transfusion protocols, the reduction in transfusions can be at least partly attributed to the tissue-sparing nature of the SuperPath procedure. This finding also agrees with the described recent multicentre study showing a substantial reduction in transfusion rates for this technique when compared to the national average in the United States [4]. Transfusions have been associated with increased complications, such as infections [8,9].…”
Section: Discussionsupporting
confidence: 92%
“…Several of these differences were attributable to the decreased length of stay observed in the SuperPath group. The average length of stay for the Lateral group (5.1 days) was over twice that of the SuperPath group (2.1 days), so it is not surprising that the costs associated with patient rooms (Lateral +60.4 %) and food services (Lateral +62.8 %) were over double for the [4]. Other cost differences, such as for transfusions, were not directly attributable to reduced length of stay.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The readmission rate at our institution was slightly lower, although comparable to other high-volume joint replacement centers that have reported 30-day readmission rates between 5% and 6% [16,20,31,32,39,44,50,61]. Although some authors have reported 30-day readmission rates as low as 2%, most of these results are for carefully selected patients with nonconventional approaches [19]. Furthermore, reviews of major databases such as the NSQIP 1 have suggested 30-day readmission rates are between 4% and 6% nationwide [49].…”
Section: Discussionsupporting
confidence: 78%
“…[38][39][40] The tissuesparing nature of this approach may allow for decreased time to ambulation, length of stay, 30-day readmission rates, in-hospital costs, and blood loss. [41][42][43] The purpose of the current study was to evaluate the incidence of dislocation at minimum one year follow up in a large series of patients undergoing primary, elective THA using the SuperPATH approach.…”
Section: Introductionmentioning
confidence: 99%